Removal and Extraction of Carboxylic Acids and Non-ionic Compounds with Simple Hydroxides and Layered Double Hydroxides - Rodriguez, Luis E.G.; Bail, Alesandro; Castillo, Rodolfo O.; Arízaga, Gregorio G.C. (Current Pharmaceutical Design, 2020)
Carboxylic acids are an important natural component as a final product or intermediates for syntheses. They are produced in plants, animals and also as products from biotechnological processes. This review presents the use of single hydroxide particles and layered double hydroxides as alternative adsorbents to remove carboxylic acids from liquid media. The proposal to use hydroxide particles is based on its affinity to adsorb or intercalate carboxylic acids. Besides, the change in properties of the adsorbate-sorbate product evinces that this intermediate can be used as a vehicle to transport and release carboxylic acids. Additional examples will also be presented to prove that layered hydroxides are capable of removing non-ionic compounds from wine, milk and tomato. The use of layered compounds to remove active ingredients could reduce the number of separations steps, costs and reduce or eliminate solvents, thus encouraging the design of industrial processes of separation using hydroxides particles.
Keywords: composite